Haglund Syndrome: A Systematic Review of the Current Possible Management - Sindi, Ghaidaa Jamil; Aldairi, Mashael Mustafa (International Journal of Innovative Research in Medical Science, 2022)
Background: Haglund’s syndrome is considered a triad of posterosuperior prominence of the calcaneus or Haglund deformity, which is also known as retrocalcaneal bursitis and insertional Achilles tendinopathy. However, many cases are resolved depending on the conservative treatment only, in patients with persistent signs and symptoms after six months of conservative management, surgery is required. In this review, we aimed to systematize the possible management of Haglund’s syndrome among studies published after the 2015. Methodology: This is a systematic review of the literature which was conducted following Cochrane Handbook of Systematic Review of Intervention and Preferred Reporting Items for a Systematic Reviews and Meta-Analyses (PRISMA) for selection of the studies. Data were extracted and recorded for a stepwise analysis from each study. Statistical analysis was conducted using IBM SPSS version 260 (IBM Corp., Armonk, N.Y., USA). Results: Through the search of literature, a total of 1474 studies were identified for initial screening. After removal of 1191 duplicated studies, preliminary evaluation was conducted among 283 papers which were available for the title and abstract screening. One- hundred- twenty-one studies (121) were excluded because being research focused on pathologies not related to Haglund’ deformity while 91 studies were excluded because reporting data on surgical management of other hindfoot condition. Therefore, 71 studies were available for full-text analysis and after application of exclusion criteria, 12 studies were available for final evaluation. Conclusion: Surgical correction of Haglund’s syndrome in case of failure of the conservative treatment provides overall good clinical outcomes with higher superiority for minimally invasive approaches which have similar good clinical outcomes in term of AOFAS, VISA, and VAS scores with less rate of complications and failure rate when compared to open surgeries.